Insights into Enhanced Oil Recovery by Polymer-Viscosity Reducing Surfactant Combination Flooding in Conventional Heavy Oil Reservoir - Yuqiu Chen; Hong He; Qun Yu; Huan Liu; Lijun Chen; Xiaorui Ma; Wenzheng Liu (Geofluids)
Polymer flooding has a significant potential to enhance oil recovery in a light oil reservoir. However, for polymer flooding in a conventional heavy oil reservoir, due to unfavorable mobility ratio between water and oil, the improvement of sweep efficiency is limited, resulting in a low incremental oil recovery and failure to achieve high-efficiency development for polymer flooding in a conventional heavy oil reservoir. Inspired by the EOR mechanisms of the surfactant-polymer (SP) flooding process, the polymer-viscosity reducing surfactant flooding (P-VRSF) system was proposed to enhance conventional heavy oil recovery. Thus, to gain an insight into enhancing oil recovery by P-VRSF in a conventional heavy oil reservoir, the viscosity property, oil-water interfacial tension property, and oil viscosity reduction property were investigated. A series of parallel sand pack experiments were conducted to investigate enhanced oil recovery ability of polymer flooding and P-VRSF in a heterogeneous reservoir. Then, the 2D micromodel flooding experiments were conducted to investigate the EOR mechanism from porous media to pore level. Results demonstrated that polymer could increase the viscosity of injection water and improve the sweep efficiency. The emulsifying stability of surfactant with ultralow IFT (10-3 mN/m) was worse than that of the surfactant with higher IFT (10-2 mN/m). The viscosity reduction rate of the surfactant with higher IFT was higher than 80% at different oil-water volume ratios. The incremental oi recovery of P-VRSF was higher than that of polymer flooding. Moreover, the polymer-viscosity reducing surfactant with higher IFT could have higher incremental oil recovery. The 2D micromodel flooding results showed that the swept area of polymer flooding and P-VRSF was larger than that of water flooding. Moreover, the swept area of the surfactant with good emulsifying stability was larger than that of the surfactant with ultralow IFT. These findings could provide insights into enhancing oil recovery by P-VRSF in the conventional heavy oil reservoir.